A Cloud-Enabled Application Framework for Simulating Regional-Scale Impacts of Natural Hazards on the Built Environment - Deierlein, Gregory G.; McKenna, Frank; Zsarnóczay, Adam; Kijewski-Correa, Tracy; Kareem, Ahsan; Elhaddad, Wael; Lowes, Laura; Schoettler, Matthew J.; Govindjee, Sanjay (Frontiers in Built Environment, 2020)
With the goal to facilitate research to evaluate the risks from natural hazards and alternate risk mitigation strategies, the Natural Hazards Engineering Research Infrastructure’s Computational Modeling and Simulation Center (NHERI SimCenter) is developing computational workflows for regional hazard simulations. These simulations enable research to integrate detailed assessments of individual facilities with comprehensive regional-scale simulations of natural hazard effects. This approach enables fine (parcel level) granularity on assessing natural hazard impacts on buildings, infrastructures systems and other constructed facilities, which can enable engineering informed assessment of policy considerations and socio-economic impacts. Effective development of research platforms for high-resolution regional simulations requires modular workflows that can integrate state-of-the-art models with information technologies and high-performance computing resources. In this paper, the modular architecture of the computational workflow models is described and illustrated through testbed applications to evaluate regional building damage under an earthquake and a hurricane scenario. Developed and disseminated as open-source software on the NHERI Design Safe Cyberinfrastructure, the computational models and workflows are enabling multi-disciplinary collaboration on research to mitigate the effects of natural hazard disasters.